RUSSIA’S FOREIGN POLICY: CENTRAL ASIA— A VIEW FROM UZBEKISTAN - PARAMONOV, Vladimir; STROKOV, Alexey; STOLPOVSKIY, Oleg (CENTRAL ASIA AND THE CAUCASUS, 2009)
The history of Russia’s policy in Central Asia is long and colorful, although the relations between Russia and Central Asia did not begin to gather momentum until the latter half of the 19th century when Central Asia became part of the Russian Empire. It was then that the region gradually established closer political, economic, cultural, and other contacts with Russia, which helped it overcome its economic and geographical isolation and added vigor to its social and economic life.The downfall of the Russian Empire opened a new era in the relations between the two parts of the same state. It was under Soviet power that the region demonstrated unprecedented economic growth and received new statehoods. In Soviet times Russia was the driving force behind the region’s social, economic, scientific, and technical progress, which shaped the region’s modern image. T Russia’s post-Soviet policy in Central Asia can be divided into three stages:At the first stage, the early and middle 1990s, Russia, guided by the illusion that it might become “part of the West,” excluded Central Asia from its foreign policy priorities;At the second stage, in the late 1990s, Russia critically assessed its earlier foreign policy and its results in all parts of the world, Central Asia included;At the third stage, which began in 2000 when Vladimir Putin and his team came to power in the Kremlin and which is continuing under President Medvedev, Russia is working consistently and purposefully toward drawing the region into its sphere of influence to boost its foreign policy position everywhere.